1983
DOI: 10.1152/ajpheart.1983.245.5.h773
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular interaction with arterial load studied in isolated canine ventricle

Abstract: We developed a framework of analysis to predict the stroke volume (SV) resulting from the complex mechanical interaction between the ventricle and its arterial system. In this analysis, we characterized both the left ventricle and the arterial system by their end systolic pressure (Ps)-SV relationships and predicted SV from the intersection of the two relationship lines. The final output of the analysis was a formula that gives the SV for a given preload as a function of the ventricular properties (Ees, V0, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
587
0
6

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 538 publications
(615 citation statements)
references
References 15 publications
10
587
0
6
Order By: Relevance
“…A more powerful and largely load‐independent measure of contractile function is LV end‐systolic elastance (E es ), which can be defined as the stiffness of the left ventricle at the end of the systole. The arterial system can also be assessed in elastance terms; hence, ventricular‐arterial coupling (VAC) can be expressed by the comparison of ventricular and arterial elastances (E a ) 12, 13, 14, 15. Experimental models showed that LV EW is maximal when the VAC (E es /E a ) ratio is 1,12 whereas the mechanical efficiency is maximal when the ratio is 2 13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…A more powerful and largely load‐independent measure of contractile function is LV end‐systolic elastance (E es ), which can be defined as the stiffness of the left ventricle at the end of the systole. The arterial system can also be assessed in elastance terms; hence, ventricular‐arterial coupling (VAC) can be expressed by the comparison of ventricular and arterial elastances (E a ) 12, 13, 14, 15. Experimental models showed that LV EW is maximal when the VAC (E es /E a ) ratio is 1,12 whereas the mechanical efficiency is maximal when the ratio is 2 13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…[8] A compliant aorta acts as a capacitor, reducing the peak pressure generated during ventricular systole and promoting continuous forward flow throughout the cardiac cycle. Central aortic pressure is further augmented during diastole by the reflected pressure wave generated downstream at the junction of the medium and small resistance arterioles.…”
Section: Vascular Dysfunction and Its Role In Acute Heart Failurementioning
confidence: 99%
“…Th is ratio was fi rst proposed by Suga [11] as a method t o evaluate the mechanical effi ciency of the cardiovascular system and the interaction between cardiac performance and vascular function. Th e Ea/Ees ratio has been consistently demonstrated to be a reliable and eff ective measure of cardiovascular performance [9,11,12]. Bur khoff and Sagawa, and successively many other investigators, have demonstrated that when the Ea/Es is near unity, the effi ciency of the system is optimal.…”
Section: Ventriculo-arterial Couplingmentioning
confidence: 99%
“…Th is optimization means that the LV workload and the arterial system optimally match when the left ventricle ejects the blood into the arterial system and is quantifi ed by ventriculo-arterial (V-A) coupling analysis. Th is process is optimized without excessive changes in LV pressure, and the mechanical energy of LV ejection is completely transferred from the ventricle to the arterial system [9,10]. Th e ro le o f V-A coupling in the management of critically ill patients with severe hemodynamic instability and shock is becoming increasingly clear.…”
mentioning
confidence: 99%